(untitled) (ARSY : Jurnal Aplikasi Riset kepada Masyarakat, 2026)
This community service program focuses on improving elementary school students’ legal and human rights literacy skills to foster early legal awareness through the provision of reading books in partner communities. This activity is motivated by the fact that legal literacy skills (through physical books) among the current generation of young people are very low. The main objective of this program is to introduce law and human rights from an early age through literacy activities by providing related physical books to partners. The implementation method uses a mini-literacy training approach, motivational lectures, and the provision of literacy resources. The activity is carried out in four stages: the review stage, the socialization stage, the activity stage, and the evaluation stage. The implementation results show an increase in students’ literacy skills and understanding of law and human rights, including an understanding of a culture of legal and human rights awareness, so that it can be implemented in everyday life. Overall, this activity makes a positive contribution to realizing increased legal and human rights literacy skills that are carried out consciously, responsibly, and can be realized in everyday life to shape legal and human rights awareness characters in students. Keyword: literacy skills, law, legal awareness, human rights, basic education